‘Skullduggery’: Lions Align and Their Mandibles Rock! - Williams, Vivienne L. (PLoS One, 2015)
South Africa has legally exported substantial quantities of lion bones to Southeast Asia and China since 2008, apparently as part of the multinational trade substituting bones and body parts of other large cats for those of the tiger in wine and other health tonics. The legal sale of lion bones may mask an illegal trade, the size of which is only partially known. An observed component of the illegal trade is that quantities of skeletons are sometimes declared falsely/fraudulently on CITES export permits. Furthermore, there are emerging concerns that bones from tigers reared in captivity in South Africa and elsewhere are being laundered as lion bones using CITES Appendix II permits. There is therefore a need for tools to monitor the trade in lion body parts and to distinguish between lions and tigers. Our research indicates that it is possible to use skeletons, skulls and cranial sutures to detect misdeclarations in the lion bone trade. It is also possible to use the average mass of a lion skeleton to corroborate the numbers of skeletons declared on CITES permits, relative to the weight of the consolidated consignments stated on the air waybills. When the mass of consolidated consignments of skeletons destined for export was regressed against the number of skeletons in that consignment, there was a strong correlation between the variables (r(2) = 0.992) that can be used as a predictor of the accuracy of a declaration on a CITES permit. Additionally, the skulls of lions and tigers differ: two cranial sutures of lions align and their mandibles rock when placed on a flat surface, whereas the cranial sutures of tigers are not aligned and their mandibles rest naturally on two contact points. These two morphological differences between the skulls of tigers and lions are easy to observe at a glance and provide a method for distinguishing between the species if illegal trade in the bones is suspected and the skulls are present. These identifications should ideally be confirmed by a DNA test to provide rigorous evidence to prosecute offenders violating CITES regulations.